Estimating amino acid limitations in California dairy rations and the effect of feeding a ruminally protected lysine supplement on animal performance - Erasmus, L.J. (Lourens Jacobus) (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2009.